2011
DOI: 10.1177/1721727x1100900107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxymatrine Combined with Low Dose 5-FU on Lymphatic Vessel and Microvascular Endothelial Cell Growth of Gastric Cancer in a Severe Combined Immunodeficient Mouse Orthotopic Implantation Model

Abstract: In this study, we explored the effect of Oxymatrine combined with low dose 5-Fu on lymphatic vessel and vascular endothelial growth factor of orthotopic implantated gastric cancer in severe combined immunodeficient (SCID) nude mice. Human gastric cancer cell line SGC-7901 was orthotopically implanted into the gastric tract of nude mice. Nude mice were treated with normal saline (control group), low dose 5-Fu, oxymatrine, oxymatrine combined with low dose 5-Fu using intraperitoneal injection. The expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“… 36 We previously confirmed the inhibitory effects of OMT on vascular and lymph node invasion in GC. 37 Herein, we found that OMT displayed anti-tumor effects via regulation of JAK/STAT signaling pathway, suggesting the potential therapeutic target for treatment of GC.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“… 36 We previously confirmed the inhibitory effects of OMT on vascular and lymph node invasion in GC. 37 Herein, we found that OMT displayed anti-tumor effects via regulation of JAK/STAT signaling pathway, suggesting the potential therapeutic target for treatment of GC.…”
Section: Introductionmentioning
confidence: 83%
“… 36 We have also reported that OMT combined with low-dose 5-fluorouracil (FU) or angiogenesis inhibitor NM-3 exhibits anti-tumor activity in GC cells. 37 , 44 Guo et al 45 have found that OMT inhibits the proliferation and invasion of GC cells via blockade of EGFR/AKT pathway. Here, we found that OMT exerted obvious anticancer effects on GC cells, which was related to inhibiting cell growth and invasion, arresting cell cycle, and inducing cell apoptosis, showing that OMT might be a novel candidate for adjuvant treatment of GC.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly known that oxymatrine exhibits many biological activities and possesses a wide range of pharmacological effects, such as anti-inflammation [ 16 ], antifibrosis [ 17 ], analgesic [ 18 ], immunosuppression [ 19 ], and antivirus [ 20 ]. Oxymatrine also has been extensively studied, for their cancer chemoprevention potentially against various cancers, for instance, gastric cancer [ 21 ], breast cancer [ 22 ], hepatocellular carcinoma [ 23 ], and pancreatic cancer [ 24 ]. However, the mechanisms of the antitumor properties of oxymatrine in laryngeal cancer are not well established to date.…”
Section: Discussionmentioning
confidence: 99%
“…IL-IFIO cDNA encodes 152-amino acid protein that shares between 41% and 43% amino acid identity with human IL-l receptor antagonist (IL-lRA). IL-IF 10 shares characteristics of the IL-l RA family, including key amino acid consensus sequences and a similar genomic structure (61)(62)(63)(64)(65). IL-IFIO mRNA is expressed in several tissue such as heart, placenta, fetal liver, spleen, thymus, and activated B cells of the human tonsil (66)(67)(68)(69)(70).…”
Section: Il-38 (Il-lflo)mentioning
confidence: 99%